2011
DOI: 10.1002/rcm.5081
|View full text |Cite
|
Sign up to set email alerts
|

Soil properties, strontium isotopic signatures and multi‐element profiles to authenticate the origin of vegetables from small‐scale regions: illustration with early potatoes from southern Italy

Abstract: We propose a method for the authentication of the origin of vegetables grown under similar weather conditions, in sites less than 10 km distance from the sea and distributed over a rather small scale area (58651 km 2 ). We studied how the strontium (Sr) isotopic signature and selected elemental concentrations ([Mn], [Cu], [Zn], [Rb], [Sr] and [Cd]) in early potatoes from three neighbouring administrative regions in the south of Italy were related to the geological substrate (alluvial sediments, volcanic subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
(27 reference statements)
1
6
0
Order By: Relevance
“…This is evident especially during the Early Gravettian, when the Sr isotope ratios of both humans and animals tend to converge towards a common lower Sr ratio, with Equus ferus as the lowest and more likely isotopic end-member. This low ratio within the considered fauna is consistent with animal movements/migrations toward the southern portion of the Apulia region (40). Zooarchaeological and taphonomic evidences of the earliest stages of the Gravettian suggest also a strong reliance on ungulates from open habitats (45).…”
Section: Gravettiansupporting
confidence: 74%
See 2 more Smart Citations
“…This is evident especially during the Early Gravettian, when the Sr isotope ratios of both humans and animals tend to converge towards a common lower Sr ratio, with Equus ferus as the lowest and more likely isotopic end-member. This low ratio within the considered fauna is consistent with animal movements/migrations toward the southern portion of the Apulia region (40). Zooarchaeological and taphonomic evidences of the earliest stages of the Gravettian suggest also a strong reliance on ungulates from open habitats (45).…”
Section: Gravettiansupporting
confidence: 74%
“…In this area, isotopic values higher than modern seawater (~0.7092) are scarcely documented and restricted to specific geological areas that include the volcanic area of Roccamonfina and the Hercynian basement outcrops of Calabria and of the easternmost portion of Sicily ( 87 Sr/ 86 Sr ratios up to ~0.71; 36,37). Instead, low Sr isotope ratios are common among Campanian, Aeolian and Etna volcanoes(38), and along the Salentine coast(39,40).Therefore, the higher and lower Sr isotope ratios endmembers found in the Gravettian teeth could derive from the exploitation of resources as far south as e.g. Calabria.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…0.71043 or higher), this Sr apparently was not mobilised so as to alter the ratios of our bone and tooth samples. It is noteworthy that the Sr signature obtained from the dental enamel of the individuals studied is consistent with data on modern botanical samples from the area of Manfredonia (Zampella et al ., ), with data from Grotta Scaloria, showing the greatest affinity by virtue of a greater range in Sr ratios (see succeeding discussions).…”
Section: Resultsmentioning
confidence: 99%
“…Sample codes are reported in Table 1. Mean modern values on vegetal species measured by Zampella et al (2011) are indicated. For the animal signatures: Sus sp.…”
Section: Resultsmentioning
confidence: 99%